Measurement of Train Driver Mental Workload Using the RNASA-TLX Method - Suhanto, Suhanto; Utomo, Bagus Wahyu; Husna, Nuzulul Latifatul; Gunawan, Gunawan; Mauidzoh, Uyuunul; Sullyartha, Esa Rengganis (Institut Teknologi Dirgantara Adisutjipto, 2024)
Efforts to develop the national railway system throughout Indonesia continue to be improved. The role of the train driver is the leading indicator of the success of transportation services in terms of safety and security. In 2015, 20% of train accidents were caused by human factors, among other causes. Therefore, it is necessary to pay attention to how much workload is given related to the demands of the task to the driver and assistant driver during their duties. This study aims to measure the mental workload of machinists and assistant machinists by distributing questionnaires using the RNASA-TLX method, which is a development of the NASA-TLX method. Overall, the results of the RNASA-TLX measurement show that the workload felt by machinists and assistant machinists is classified as high mental workload, with the WWL score obtained in the value range of 50-79. Mental demands dominate the high cognitive workload of machinists, while visual demands dominate assistant machinists. From the t-test results, there is no significant difference, meaning that both machinists and assistant machinists have high task demands, so a leadership policy is needed in an effort to reduce the mental workload